2009
DOI: 10.1051/apido/2009024
|View full text |Cite
|
Sign up to set email alerts
|

A scientific note on E-β-ocimene, a new volatile primer pheromone that inhibits worker ovary development in honey bees

Abstract: E-β-ocimene / ovary development / pheromone / brood / Apis mellifera Note scientifique sur une nouvelle phéromone modificatrice volatile qui inhibe le développement ovarien des abeilles, le E-β-ocimene. 564A. Maisonnasse et al. Eine wissenschaftliche Notiz über E-β-ocimene, ein neues flüchtiges Primer-Pheromon, das dieOvarentwicklung der Honigbienen hemmt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 14 publications
6
64
1
Order By: Relevance
“…The reproduction of normal workers in queenless colonies is not surprising; it is well known that up to 30% of workers can activate their ovaries and lay unfertilized, male-destined eggs (Ratnieks 1993). The activation of worker ovarioles in an orphaned nest is determined by declines in the levels of queen and brood pheromones (Hoover et al 2003;Maisonnasse et al 2009). The similar number of workers' sons observed between queenright subunits with rebel workers and queenless subunits with normal workers suggests that rebel workers have a higher reproductive capacity than do normal workers.…”
Section: Discussionmentioning
confidence: 99%
“…The reproduction of normal workers in queenless colonies is not surprising; it is well known that up to 30% of workers can activate their ovaries and lay unfertilized, male-destined eggs (Ratnieks 1993). The activation of worker ovarioles in an orphaned nest is determined by declines in the levels of queen and brood pheromones (Hoover et al 2003;Maisonnasse et al 2009). The similar number of workers' sons observed between queenright subunits with rebel workers and queenless subunits with normal workers suggests that rebel workers have a higher reproductive capacity than do normal workers.…”
Section: Discussionmentioning
confidence: 99%
“…BP and EBO are chemically distinct larval pheromones, but they can induce similar physiological and behavioral changes in nurse bees. For instance, Maisonnasse et al (2009Maisonnasse et al ( , 2010 showed that EBO partially suppresses worker ovary development and accelerates the behavioral transition from nursing to foraging, which is similar to the long-term physiological effects of low doses of BP. This transition is delayed in the presence of high doses of BP, however.…”
Section: Introductionmentioning
confidence: 85%
“…Honey bee larvae also emit (E )-β-ocimene (EBO), a volatile monoterpene produced primarily by young larvae in their first through third instar (Maisonnasse et al 2009(Maisonnasse et al , 2010. Like other volatile pheromones, EBO can dissipate quickly.…”
Section: Introductionmentioning
confidence: 99%
“…All of the ten esters (boiling point around 200 °C) generally known as brood pheromone are non-volatile and their movement is likely facilitated by worker to worker contact (Pankiw, 2004a;Maisonnasse et al, 2010). Very recently, a new highly volatile molecule, E-β-ocimene, has been identified in larvae (Maisonnasse et al, 2009). This brood pheromone component also acts as a primer pheromone with two actions on worker bee physiology: inhibition of worker ovaries (Maisonnasse et al, 2009) and acceleration of worker bee behavioural maturation (Maisonnasse et al, 2010).…”
Section: Interactions Between Adults and Broodmentioning
confidence: 99%
“…Very recently, a new highly volatile molecule, E-β-ocimene, has been identified in larvae (Maisonnasse et al, 2009). This brood pheromone component also acts as a primer pheromone with two actions on worker bee physiology: inhibition of worker ovaries (Maisonnasse et al, 2009) and acceleration of worker bee behavioural maturation (Maisonnasse et al, 2010). E-β-ocimene (boiling point 73 °C), which belongs to the terpene family, is volatile so and therefore has an aerial transmission and is easily dispersed within the colony (Maisonnasse et al, 2010).…”
Section: Interactions Between Adults and Broodmentioning
confidence: 99%